Determination of slip melting point in palm oil blends by partial least squares and principal component regression modeling of FTIR spectroscopic data - Setiowaty, G.; Che Man, Y.B. (Wiley, 2002)
The determination of slip melting point (SMP) in refined, bleached, and deodorized palm oil is a common and regular requirement in the manufacture of this oil. An FTIR spectrometer in the mid-IR wavelength region (4000-750 cm-1) can provide the basis for a suitable on-line and off-line quantitative analytical methodology if used with a suitable calibration model. In this study, by using data from selected regions, the calibration models, including principal component regression and partial least squares regression, have been examined and evaluated for efficacy in determining SMP directly in palm oil blends. Results indicate that orthogonal models using selected wavelength data offer superior predictive performance.